Considering the role of the energy grid mix on indirect water use in dairy barns - Rajan Ray; Etienne Le Riche; Robert Gordon; Andrew VanderZaag (Energy Nexus)
Water use is an important environmental concern for the dairy sector. There are two kinds of water use in the dairy sector, direct and indirect. Electricity generation (e.g., cooling water, evaporation, etc.) is an indirect use of water and a significant contributor to the overall water budget depending on how electricity is generated. In Canada, the dairy industry is distributed across 10 provinces each with a wide range of electricity generation sources in their grid mix, making it an interesting case study. For a dairy farm that uses 1021 kWh cow-1 y-1 (9.4 – 10.6 kWh per 100 kg milk, depending on the province), the average water use related to generating electricity was estimated to be 3.48 L kg-1 milk (range: 1.40 – 5.77 L kg-1, depending on the electricity grid). Energy conservation technologies could reduce electricity use by as much as 30 % and thus reduce water use by 1.04 L kg-1 milk on average (range: 0.42 – 1.73 L kg-1). Installing an on-farm solar array (0.40 kWp cow-1; i.e. one 400-watt solar panel per cow) could lower grid-electricity-related water use by 35 – 51 % (or by 0.57 – 2.71 L kg-1). Solar array sized with the capacity to reach net-zero electricity is feasible and can eliminate grid-electricity-related water use. This study highlights that dairy farms can achieve substantial water savings by strategically using electricity conservation and renewables, with the magnitude depending on the electricity grid mix, a relationship that has yet to be analyzed in current literature.